Nonlinear Schrödinger Equation for Description of Small-amplitude Spin Waves in Multilayer Magnetic Materials - I.V. Gerasimchuk; Yu.I. Gorobets; V.S. Gerasimchuk (Журнал нано- та електронної фізики)
In the framework of the description of spin waves in multilayer magnetic materials the nonlinear Schrödinger equation with the system of -functional potentials was derived. In the case of a system with one narrow magnetic layer (“magnetic sandwich”), having different value of single-ion anisotropy from that one of the matrix, the corresponding boundary conditions are obtained and the solution localized near this layer is found. The properties are described and the quasi-classical quantization of the obtained soliton state is carried out.